PENGEMBANGAN ENSIKLOPEDIA TANAMAN ANYAMAN SUKU MELAYU KABUPATEN NATUNA - Serly Marsa lena; Ari Sunandar; Mahwar Qurbaniah (Postgraduate, University of Mataram, 2024)
The Malay tribe community in Natuna Regency still preserves one of the cultures, namely weaving several products that are used as tools to support their daily needs. This study aims to determine the validity of the encyclopedia of woven plants of the Malay tribe in South Bunguran District, Natuna Regency and to determine student responses to the encyclopedia of woven plants of the Malay tribe in South Bunguran District, Natuna Regency. The method used is design and development (D&D). Based on the results of the research that has been done, it is found that the media encyclopedia of woven plants of the Malay tribe of Natuna Regency has fulfilled the validity aspects where the media aspect is 95.29% (very valid), the material aspect is 96.67% (very valid), and the linguistic aspect is 97.27% (very valid). Learners gave a very good response where on a small scale trial and a large scale got a small scale score of 91.04% (Very good) and a large scale of 93.50% (Very good). It can be concluded that the encyclopedia of woven plants of the Malay tribe in Natuna Regency can be utilized as a biology learning media that is included in biodiversity material.